Ma’i Lepera : Representation of Leprosy in selected Hawai’ian-American Literature - Kristiawan Indriyanto (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2022)
This study contextualizes how disease in form of leprosy is represented in literary works by focusing of three novels written by Hawai’ian-American writers. The legacy of leprosy outbreak in Hawai’ian archipelago in the 1800’s challenges the popular imagination of Hawai’i as idealized timeless tropical paradise. This study explores how the policy of isolation exiles leprosy patients in isolated island, Moloka’i, segregated from other citizens. Hawai’ians cultural contexts concerning balance (pono), and identity based on familial ties and sense of place is employed to explore how leprosy disrupts Hawai’ian conception of identity. This study also explores the concept of ecological other as theorized by Serpil Oppermann to contextualize the stigma and harassment associated with leprosy of being unclean and contagious. The object of this study are three Hawai’ian-American novels, Hawai’i (1959), Shark Dialogues (1995) and Moloka’i (2004). This study concludes that the representation of leprosy in selected Hawai’ian-American literature contextualizes the social stigma associated toward its sufferers and disrupts the question of identity through erasure of familial history and genealogy. It further posits the possibility of reclaiming genealogy, history and ancestry lost due to leprosy and how the reclamation results in creating hybrid Hawai’ian identity.